(untitled) (Orfeu, 2020)
The present article presents results of creative processes regarding vocal arrangement based on the compositional elements of Clube da Esquina. Thus, it aims to expose the artistic possibilities that can emerge from the exploration of the idea that stylistic analysis can also be inserted as a relevant resource within the dynamics of apprehension and experimentation of the musical structuring parameters inherent to the process of creating arrangements for groups vocals. The first arrangement was for the song Milagre dos Peixes by Milton Nascimento and Fernando Brant and the second for the song Chovendo na Roseira by Tom Jobim. Finally, a brief discussion theoretical-reflective is presented about the possibilities that such an approach could offer in this research and perspectives on creative processes within the scope of the vocal arrangement of urban popular music.